Effects of hydrotherapy and Hammock positioning on weight gain in low-birth-weight premature newborns: a randomized clinical trial - Jeferson de Sousa Justino; Francisco Plácido Nogueira Arcanjo; Luiz Odorico Monteiro de Andrade; Ivana Cristina de Holanda Cunha Barreto; Lizandro de Andrade Teles; Ana Talita Vasconcelos Arcanjo; Edcley Sousa Teixeira; Marya Clara Barros Mororó (Jornal de Pediatria)
Objective: To evaluate and compare whether hydrotherapy and hammock positioning techniques assist in the weight gain of premature newborns. Methodology: A single-blind randomized clinical trial was conducted at Santa Casa de Misericórdia Hospital in Sobral, between July 2022 and October 2023. The trial included 16 months of data collection and involved seventy-six premature newborns with low birth weight, of which only sixty were included after meeting the inclusion criteria. These newborns were randomly divided into four groups: one control group and three groups that received different intervention techniques (hydrotherapy, hammock positioning, and a combined group of hydrotherapy and hammock positioning). The newborns were monitored for clinical stability and specific signs before and after the interventions. The techniques were applied daily for 15 days. Results: During the 15-day follow-up, the control group had a mean weight gain of 305 g. The group that received hydrotherapy gained 346 g, but without significance. The hammock group and the combined hydrotherapy and hammock group showed significant weight gains: the hammock group had an increase of 360 g (p = 0.011), while the combined group achieved a gain of 616 g (p = 0.0001). Significant increases in arm circumferences were observed in the hammock group and the hydrotherapy combined with the hammock positioning group. Conclusion: The results indicate that the combination of hydrotherapy and hammock positioning leads to a significant increase in weight gain in premature newborns. The isolated use of hammock positioning also showed positive effects, but the isolated use of hydrotherapy did not yield significant results (Brazilian Registry of Clinical Trials RBR-6 g5f4jz).